Protective Effect of the Hydrophilic Extract of Polypodium leucotomos, Fernblock®, against the Synergistic Action of UVA Radiation and Benzo[a]pyrene Pollutant - María Gallego-Rentero; Jimena Nicolás-Morala; Miguel Alonso-Juarranz; Elisa Carrasco; Mikel Portillo-Esnaola; Azahara Rodríguez-Luna; Salvador González (MDPI AG, 2022)
Oxidative stress is a harmful effect induced on the skin by polycyclic aromatic hydrocarbons (PAH), including benzo[a]pyrene (BaP) air pollutants. This effect is amplified by the additive damaging effect of the sun, especially through the UVA light component. Besides being one of the main compounds that make up air pollution, BaP can also be found in tar, tobacco smoke, and various foods. In addition to its direct carcinogenic potential, BaP can act as a photosensitizer absorbing sunlight in the UVA range and thus generating ROS and 8-hydroxy-2'-deoxyguanosine (8-OHdG). Fernblock® (FB) is an aqueous extract from the leaves of Polypodium leucotomos that has been proven to exert photoprotective and antioxidant effects on skin cells. In this study, we evaluate the potential of FB to prevent the damage induced by a combination of BaP and UVA light on human keratinocyte and mouse melanocyte cell lines (HaCaT and B16-F10, respectively). In particular, we have analyzed the capacity of FB to counteract the alterations caused on cellular morphology, viability, oxidative stress and melanogenic signaling pathway activation. Our data indicate that FB prevented cell damage and reduced oxidative stress and melanogenic signaling pathway activation caused by a combination of BaP and UVA light irradiation. Altogether, our findings support the fact that FB is able to prevent skin damage caused by the exposure to a combination of UVA and the air pollutant BaP.